MENINGKATKAN KEAKTIFAN DAN KERJA SAMA KELOMPOK SISWA MENGGUNAKAN TEKNIK eMeLGr DALAM MEMBANDINGKAN DAN MENYUSUN GREETING CARD - Arie Rahmawati (Padma Sari: Jurnal Ilmu Pendidikan, 2022)
The purpose of this scientific work of learning is to find out whether the use of eMeLGr techniques can increase the activeness of student group cooperation in comparing and composing greeting cards and how the use of eMeLGr techniques to improve the activeness of student group cooperation in comparing and composing greeting cards. The eMeLGr technique is implemented for basic competencies of comparing and composing greeting cards. In its implementation the eMeLGr technique is applied with the Jigsaw learning model. The type of research used is descriptive, that is, it describes the description and explanation systematically. The descriptive method used in this study also aims to examine the current situation related to increasing the activeness and cooperation of student groups using the eMeLGr technique in comparing and compiling greeting cards The learning process of comparing and composing greeting cards of students of class VIII-K SMPN 2 Sidoarjo went smoothly. The result of the use of eMeLGr techniques in English learning in comparing and composing greeting cards is the activeness of student group cooperation increased. This is evidenced by the results of observations of the activeness of increased student group cooperation. The average achievement of activeness of student group cooperation increased through these techniques.